2015
DOI: 10.1016/s2213-2600(15)00435-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of human immunisation with a live-attenuated Mycobacterium tuberculosis vaccine: a randomised, double-blind, controlled phase I trial

Abstract: Background Tuberculosis remains one of the world's deadliest transmissible diseases despite the widespread use of BCG. MTBVAC is a new live tuberculosis vaccine based on a genetically attenuated phoP-/fadD26-deletion mutant of M. tuberculosis that expresses most antigens present in human isolates in contrast to BCG. Methods We conducted this randomized, double-blind, controlled phase I study at CHUV, Lausanne, Switzerland, to compare MTBVAC to BCG in healthy, PPD-negative adults. Primary outcome was safety in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 27 publications
(32 reference statements)
2
116
0
2
Order By: Relevance
“…2.5×10 7 CFU. By this route and dose of administration, all data showed comparable safety and attenuation profile for MTBVAC (and SO2) and BCG SSI, which is the strain used as control comparator in MTBVAC phase I clinical evaluation in adults [70] and in newborns (NCT02013245). Additionally, biodistribution and formal toxicity studies showed that intradermal inoculation of MTBVAC presents lack of toxicity, limited organ biodistribution and persistence, and untraceable excretion in urine and stool up to six months post vaccination, comparable to BCG SSI, as well as appears to be less reactogenic than BCG in mice and guinea pigs [39].…”
Section: Preclinical Characterization Of Mtbvacmentioning
confidence: 83%
See 4 more Smart Citations
“…2.5×10 7 CFU. By this route and dose of administration, all data showed comparable safety and attenuation profile for MTBVAC (and SO2) and BCG SSI, which is the strain used as control comparator in MTBVAC phase I clinical evaluation in adults [70] and in newborns (NCT02013245). Additionally, biodistribution and formal toxicity studies showed that intradermal inoculation of MTBVAC presents lack of toxicity, limited organ biodistribution and persistence, and untraceable excretion in urine and stool up to six months post vaccination, comparable to BCG SSI, as well as appears to be less reactogenic than BCG in mice and guinea pigs [39].…”
Section: Preclinical Characterization Of Mtbvacmentioning
confidence: 83%
“…This calls for significant considerations for the potential implications of the current Quantiferon assay for in vitro diagnosis of TB infection (based on ESAT-6, CFP-10 and TB7.7) in MTBVAC clinical trials in TBendemic regions. Relevant to this, in the MTBVAC phase Ia trial in adults in Lausanne, ELISpot conversion data to PPD, and to separate antigens ESAT-6 and CFP-10 showed responses to ESAT-6 that stayed below threshold for a positive test readout of infection with M. tuberculosis, while there was a transient increase in CFP-10-specific IFNγ response over the limit of positivity in two of nine subjects from the intermediate MTBVAC dose group (5×10 4 CFU) and in one subject of MTBVAC high-dose group (5x10 5 CFU) at day 28, which at day 270 (end of study) was below threshold for M. tuberculosis infection [70]. These results are supported by recent data in goats where vaccination with SO2 induced a transient ESAT-6/ CFP-10 positivity in 50% of the animals [82].…”
Section: The Quantiferon Tb-diagnostic Test and Implications For Mtbvmentioning
confidence: 90%
See 3 more Smart Citations